Pemberdayaan kelompok ibu Toloweri Kelurahan Nungga dalam pembinaan terpadu penyakit tidak menular - Hayati, Zahratul (ARKA INSTITUTE, 2022)
This Community Service (PKM) activity is carried out in an effort to provide additional knowledge and understanding about the development of PTM Posbindu which is an integrated part of the health service system based on PTM problems that exist in the community which includes promotive and preventive efforts as well as referral patterns. Posbindu PTM is community participation in carrying out early detection and monitoring of PTM risk factors that are carried out in an integrated, routine, and periodic manner for the elderly in the Toloweri community, Nungga Village, East Rasanae District, Bima City, West Nusa Tenggara. Activities are carried out using the lecture method, and answer questions, and direct practice. At the end of the activity, a final evaluation is held. This evaluation is measured based on the activities of the participants during the activity. The results of this PKM activity make mothers know and understand the health service system based on PTM problems that exist in the community which include promotive and preventive efforts as well as referral patterns. Posbindu PTM is the participation of the community in carrying out early detection and monitoring of PTM risk factors that are carried out in an integrated, routine, and periodic manner. In general, this service activity is said to be successful if at least 80% of the service participants are present and fully participate in the activity. In addition, PKM implementers collaborate with PKL Students at the Midwifery Academy, Surya Mandiri Bima, as a form of concern for the prevention of non-communicable diseases.